Exploring the Issues of Gender Identity and Pronouns in Modern American Society - Ammari, Ali; Touil, Ali (University of Eloued جامعة الوادي, 2024)
The present study examines one of the most debated topics around the world particularly in American society which is the issue of gender identity and pronouns in modern American society. It focuses on the main roots and background of non-binary and gender-neutral pronouns. The qualitative approach is used to investigate and refer to various studies and perspectives—historical, linguistic, psychological, social, and legal—pertaining to this issue. The study underscores the multifaceted roots of gender identity and pronouns and highlights their connection to the women's rights movement. Thus, the present study explores significant factors that play essential roles that led to the spread of gender and pronoun misuse. The study's discussion part delves into future negative expectations of gender-neutral pronouns, and non-binary pronouns usage and its impacts on contemporary and next generations of American society. Further research is necessary to gain a deeper understanding of the American society for the next generations, particularly the Arabic world. تتناول هذه الدراسة أحد أكثر المواضيع إثارة للجدل حول العالم وخاصة في المجتمع الأمريكي وهي قضية الهوية الجندرية والضمائر في المجتمع الأمريكي الحديث. وركز على الجذور والخلفية الرئيسية للضمائر غير الثنائية والمحايدة بين الجنسين. وتم استخدام المنهج النوعي للتحقيق والإشارة إلى مختلف الدراسات ووجهات النظر – التاريخية واللغوية والنفسية والاجتماعية والقانونية – المتعلقة بهذه القضية. تؤكد الدراسة على الجذور المتعددة الأوجه للهوية الجندرية والضمائر وتسلط الضوء على ارتباطها بحركة حقوق المرأة. ومن ثم، فإن الدراسة الحالية تستكشف العوامل المهمة التي تلعب أدوارًا أساسية أدت إلى انتشار سوء استخدام النوع الجنسي والضمائر. يتطرق الجزء التحليلي للدراسة إلى التوقعات السلبية المستقبلية للضمائر المحايدة جنسانيًا، واستخدام الضمائر غير الثنائية وتأثيراتها على الأجيال المعاصرة والقادمة من المجتمع الأمريكي. ومن الضروري إجراء المزيد من الأبحاث للحصول على فهم أعمق للمجتمع الأمريكي للأجيال القادمة، وخصة العالم العربي.
Literature and Civilization
Keywords: American Society; Gender Identity; Non-Binary Pronouns; المجتمع الأمريكي، الهوية الجندرية، الضمائر غير الثنائية